(untitled) (Revista Brasileña de Terapia Comportamental y Cognitiva, 2007)
The Skinnerian analysis of verbal behavior involved the production of a classificatory scheme of the relations between responses and environment that would be its unit of analysis – the verbal operants. From the characterization of the control relation called audience by Skinner in Verbal Behavior (1957), two basic aspects, necessary to comprehend this concept, were identified: a) the consideration of audience as another verbal operant and b) the consideration of audience as a relation of additional control (conditional stimulation or establishing operation) for other relations – mand , tact, echoic, intraverbal and textual. In both situations, it is intended to enlighten the possible implications that the recognition of the specified relation could mean in terms of conceptual elaboration and the importance to recognize theses relations.